Introduction. “Learning to Learn from Below”: Understanding Subalternity - Thapan, Meenakshi (South Asia multidisciplinary academic journal, 2022)
In a remarkable commentary on the “new” subaltern, Gayatri Chakravarty Spivak examines the question of “subaltern consciousness” not as subject consciousness but in terms of “social agency—institutionally validated action” taking democracy and development as the two most urgent concerns (Spivak 2012a). Spivak sets out to do this by “learning to learn from below.” If considered in its transparent, most direct state, this is the task that scholars must engage with so as to speak with the subalt...